Comparison of family centered care with family integrated care and mobile technology (mFICare) on preterm infant and family outcomes: a multi-site quasi-experimental clinical trial protocol - Linda S. Franck; Rebecca M. Kriz; Robin Bisgaard; Diana M. Cormier; Priscilla Joe; Pamela S. Miller; Jae H. Kim; Carol Lin; Yao Sun (BMC, 2019)
Abstract Background Family Centered Care (FCC) has been widely adopted as the framework for caring for infants in the Neonatal Intensive Care Unit (NICU) but it is not uniformly defined or practiced, making it difficult to determine impact. Previous studies have shown that implementing the Family Integrated Care (FICare) intervention program for preterm infants in the NICU setting leads to significant improvements in infant and family outcomes. Further research is warranted to determine feasibility, acceptability and differential impact of FICare in the US context. The addition of a mobile application (app) may be effective in providing supplemental support for parent participation in the FICare program and provide detailed data on program component uptake and outcomes. Methods This exploratory multi-site quasi-experimental study will compare usual FCC with mobile enhanced FICare (mFICare) on growth and clinical outcomes of preterm infants born at or before 33 weeks gestational age, as well as the stress, competence and self-efficacy of their parents. The feasibility and acceptability of using mobile technology to gather data about parent involvement in the care of preterm infants receiving FCC or mFICare as well as of the mFICare intervention will be evaluated (Aim 1). The effect sizes for infant growth (primary outcome) and for secondary infant and parent outcomes at NICU discharge and three months after discharge will be estimated (Aim 2). Discussion This study will provide new data about the implementation of FICare in the US context within various hospital settings and identify important barriers, facilitators and key processes that may contribute to the effectiveness of FICare. It will also offer insights to clinicians on the feasibility of a new mobile application to support parent-focused research and promote integration of parents into the NICU care team in US hospital settings. Trial registration ClinicalTrials.gov, ID NCT03418870. Retrospectively registered on December 18, 2017.